The Role of Board Composition on ESG Disclosure: An Analytical Study in Indonesia - Iskandar Itan; Rendy Diaz Hilrian; Mariska Ramadana (Politeknik Ganesha Medan, 2025)
Market capitalization and Environmental, Social, and Governance (ESG) disclosure have become increasingly interconnected in contemporary corporate governance, yet the mechanisms through which board composition influences ESG transparency in emerging markets remain insufficiently explored. This study examines the relationship between board characteristics and ESG disclosure quality among Indonesian listed companies, specifically analyzing how these relationships manifest across different market capitalization thresholds. Using panel data regression analysis of 256 observations from 64 Indonesian Stock Exchange companies over 2019-2022, this research investigates the effects of board size, board meetings, female board representation, audit committee size, nomination and remuneration committee size, and board compensation on ESG disclosure practices. The study addresses a critical research gap by providing empirical evidence from Indonesia's underrepresented emerging market context, where corporate governance structures and disclosure practices differ markedly from Western frameworks. Results reveal that market capitalization demonstrates no significant impact on ESG disclosure quality, contradicting conventional expectations. Board size and female director representation exhibit unexpected negative relationships with ESG disclosure, suggesting coordination challenges and potential tokenistic appointments within Indonesian contexts. Conversely, audit committee size, nomination and remuneration committee size, and board compensation demonstrate robust positive associations with ESG transparency, highlighting their critical roles in enhancing oversight capacity and aligning managerial incentives. This research contributes theoretically by challenging universal governance prescriptions and demonstrating contextual variations in board mechanism effectiveness within emerging economies. Practically, findings suggest Indonesian corporations should prioritize committee-based governance structures and performance-linked compensation over numerical board expansion. Policymakers should emphasize substantive governance effectiveness through director training and accountability mechanisms rather than mandating demographic diversity targets alone. Future research should pursue longitudinal analysis and qualitative investigations to illuminate temporal dynamics and cultural mechanisms underlying governance-ESG relationships in Southeast Asian markets.